Obstructive Fibrinous Tracheal Pseudomembrane. (July 2017) - Ammar, Yoann; Vella-Boucaud, Juliette; Launois, Claire; Vallerand, Hervé; Dury, Sandra; Lebargy, François; Deslee, Gaëtan; Perotin, Jeanne-Marie
Abstract : Obstructive fibrinous tracheal pseudomembrane (OFTP) is a rare and potentially severe complication of endotracheal intubation characterized by a tubular pseudomembrane that obstructs the trachea and induces clinical symptoms of airway obstruction after extubation. In this report, we reviewed and summarized all published cases of OFTP (n = 58) between 1981 and 2015. Twenty-three of 52 patients were men, and the mean age was 36 ± 22 years. Intubation was emergent in 41 of 53 cases. OFTP was revealed by acute symptoms in 19 of 39 cases and led to acute respiratory failure in 13 of 39 cases. Symptoms occurred 3 ± 3 days after extubation. A tracheal obstruction ≥70% was observed in 14 of 18 cases. Bronchoscopic removal was performed in 49 of 58 cases with no recurrence. In conclusion, OFTP is characterized by a typical clinical and endoscopic presentation, with no recurrence after bronchoscopic removal. Early recognition and bronchoscopy are key elements for efficient diagnosis and treatment. Abstract : Published ahead of print June 1, 2016.